ANALISIS FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI, PENGELUARAN PEMERINTAH DAN INVESTASI SWASTA DI INDONESIA - Yuliarti, Yuliarti; Amar, Syamsul; Idris, Idris (Jurnal Kajian Ekonomi, 2015)
This article focused on analyze (1) Effect of consumption, nett export, labor, government expenditure and the private investment to the economic growth in Indonesia. (2) Effect of interest rate, inflation, kurs and economic growth to the government expenditure in Indonesia (3).Effect  of  interest rate, inflation  and economic growth  to the private investment inIndonesia. Data used time series of (1984–2013). This article use analyzer model equation of simultaneous with method of Two Stage Least Squared (TSLS).The result of research concludes that (1) the consumption  have a significant and positive impact on the economic growth, while net export is not significant and positive impact to the economic growth, labor is not significant and positif impact to the economic growth, government expenditure have significant and positive to the economic growth and private investment have a significant and negative impact on the economic growth in Indonesia. If the economic growth increases, the consumption will also increase. (2) The interest rate is not significant and negative impact to the government expenditure, inflation and kurs have significant and negative impact to the government expenditure, while economic growth have significant and positive impact to the government expenditute in Indonesia. (3)The interest rate and inflation have significant and negatif impact to the private investment, while economic growth have and positive impact to the private investment in Indonesia .  Keywords : Economic growth, government expenditure and private investment